2018 IEEE/OES Autonomous Underwater Vehicle Workshop (AUV) 2018
DOI: 10.1109/auv.2018.8729778
|View full text |Cite
|
Sign up to set email alerts
|

A Natural Language Interface with Relayed Acoustic Communications for Improved Command and Control of AUVs

Abstract: Autonomous underwater vehicles (AUVs) are being tasked with increasingly complex missions. The acoustic communications required for AUVs are, by the nature of the medium, low bandwidth while adverse environmental conditions underwater often mean they are also intermittent. This has motivated development of highly autonomous systems, which can operate independently of their operators for considerable periods of time. These missions often involve multiple vehicles leading not only to challenges in communications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The final demonstration in the Atlantic Ocean involved ten heterogeneous vehicles but all the technologies designed during the project were conceived and implemented with a specific long term vision: underwater missions performed by a large number of autonomous cooperating robots. Moreover, the system presented in Robb et al (2018) dealt with the difficulty of monitoring multi-objective, multi-vehicle operations, while at the same time resolving the ambiguity about the actual status and the protection of distant, high-value platforms. In order to increase the reliability and efficacy of UMV C2S, the authors suggested a hybrid of an interactive, natural language operator interface coupled with communications using multi-domain channels to transmit data through various devices and delivery modes, enhancing C2 of coordinated and ultimately autonomous missions.…”
Section: Interoperability Background and Relevant Literaturementioning
confidence: 99%
“…The final demonstration in the Atlantic Ocean involved ten heterogeneous vehicles but all the technologies designed during the project were conceived and implemented with a specific long term vision: underwater missions performed by a large number of autonomous cooperating robots. Moreover, the system presented in Robb et al (2018) dealt with the difficulty of monitoring multi-objective, multi-vehicle operations, while at the same time resolving the ambiguity about the actual status and the protection of distant, high-value platforms. In order to increase the reliability and efficacy of UMV C2S, the authors suggested a hybrid of an interactive, natural language operator interface coupled with communications using multi-domain channels to transmit data through various devices and delivery modes, enhancing C2 of coordinated and ultimately autonomous missions.…”
Section: Interoperability Background and Relevant Literaturementioning
confidence: 99%